Central nervous system posttransplant lymphoproliferative disorder following allogeneic hematopoietic stem cell transplantation successfully treated with combination therapy of acalabrutinib and immunochemotherapy: A case report and literature review - Peihao Zheng; Teng Xu; Xiaona Zuo; Xiaoyan Ke; Kai Hu (eJHaem)
Abstract Here, we report a case of Epstein‐Barr virus‐positive central nervous system‐post‐transplant lymphoproliferative disorder (CNS‐PTLD) patient who failed to achieve complete metabolic remission (CMR) after successively trying a methotrexate‐based regimen combined with orelabrutinib or whole‐brain radiotherapy and encountered intracranial hemorrhage during orelabrutinib treatment. Ultimately, the patient achieved CMR after one cycle of acalabrutinib in combination with temozolomide, teniposide, liposomal doxorubicin, dexamethasone, and rituximab (TEDDi‐R). Following another cycle of TEDDi‐R treatment, he has been receiving acalabrutinib maintenance up to now and remained in CMR. The case may provide an effective treatment option for CNS‐PTLD patients in clinical practice.